Poor Imitative Performance of Unlearned Gestures in Children with Probable Developmental Coordination Disorder - Reynolds, J.; Kerrigan, S.; Elliott, Catherine; Lay, B.; Licari, M. (2016)
It has been hypothesized that deficits in imitation, linked to abnormal functioning of the mirror neuron system (MNS), may contribute to the motor impairments associated with developmental coordination disorder (DCD). The authors aimed to examine imitation of complex novel postures and sequences of gestures in children with and without probable DCD (pDCD), using the postural praxis and sequencing praxis subtests of the Sensory Integration and Praxis Tests (Ayres, 1989). Participants were 29 boys with pDCD between 6.08 and 13.33 years old, and 29 group age-matched typically developing boys between 6.08 and 13.83 years old. Responses of children with pDCD on both imitation tasks were less accurate than controls, with group differences more apparent with increasing task complexity. Furthermore, as a group, children with pDCD were slower and had a higher number of non–mirror-imitated responses. There was considerable variability within the pDCD group, with some children displaying imitation scores within the normative range. Given the importance of imitation and visual learning for motor development, the difficulties in imitation displayed by some children with pDCD have the potential to impact on movement acquisition. Interventions to target imitation may be beneficial for these children. The results show that children with pDCD had difficulty imitating complex novel postures, children with pDCD had difficulty imitating gesture sequences, children with pDCD had slower responses than controls, group differences in imitation performance increased with task complexity, and not all children with pDCD displayed imitation deficits.